Aspects of Violence and Violent Behaviour Related to Criminal Law and Criminology - Igrački, Jasmina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
This paper deals with violence and violent behavior from the perspective of criminology and criminal law. According to a rule, violence is characterized by the use of force and it is commonly used as a tool to achieve a certain goal. In the sphere of criminal law, violence relates to those incriminated human behavior which are violating and jeopardizing legally protected goods by the use of force or serious threat. Studying violent behavior as one of the most intriguing phenomena of contemporary civilization is particularly significant for interpretation and understanding of human behavior and social environment. Studies on violence, its causes and strategies of prevention organized by the World Health Organization show that the causes are in the personality of the offender, social environment, familial relationships, system of values and culture of certain social groups. The seriousness of violent behavior committed by individuals or groups is also proved by the fact that violence is one of the main causes of death in all parts of the world.